Chivalrous idealist and pragmatic strategist: the influence of Mohist values on Ma Yun's leadership in China. Issue 2 (15th March 2019) - Zhou, Yaping; Kim, Suwan; Rui, Donggen
ABSTRACT: In the study of leadership within the private sector in China, few scholars have tried to link ancient Chinese teachings to the present leadership style beyond the level of highlighting Confucianism and/or militarist philosophy. This study argues that Mohist teachings are the foundation of Ma Yun's leadership in Alibaba.com. Using three propositions of (a) Ma Yun's motivation to become a start-up CEO, (b) structuring his business using his inter-national skills and linguistic competences and (c) shaping his leader-ship style based on the Mohist teachings, one of the minority schools of ancient Chinese philosophy, this paper finds that innovative firms in China such as Alibaba.com deliberately shies themselves from conventional symbols of Confucianism or militarist teachings to accommodate Western managerial in the name of unpopular ancient Chinese teachings. The result of Ma Yun's leadership is successful corporate social responsibility (CSR) performance amid rapid innovation within his company. Our results show that Ma Yun's Mohist quality and balance of justice and interests are the most effective measurement indicators of Ma Yun's internal operations; values of eloquent rhetoric, a chivalrous spirit, and mutual love have promoted Alibaba's external reputation and expansion and constitute important indicators.